Synthesis of hydroxamic fatty acids (FHA) from coconut oil using lipase as a catalyst - Henri Macandal (Global Writing Academica Researching and Publishing, 2024)
Social communication uses verbal and non-verbal language. We examined the degree of confidence and brain activity when verbal and facial expressions are incongruous. Fourteen healthy volunteers viewed photographs of 8 people with pleasant (smile) or unpleasant (disgust) expressions alone or combined with a verbal expression [positive/negative]. As an index of trust, subjects were asked to offer a donation when they were told that the person in the photo was in financial difficulty. Positive emotions and confidence were assessed using the visual analogue scale (VAS). Event-related potentials (ERPs) were obtained at 170–240 ms after viewing the photographs. Brain activity in incongruent conditions was localized using standardized low-resolution brain electromagnetic tomography (sLORETA). The VAS scores for the × positive smile condition were significantly higher than those for the other conditions (< 0.05). Gift giving was significantly lower for incongruence between verbal and facial expressions, particularly for the × negative smile condition. The EEG showed more activity in the parietal lobe with incongruent conditions than with congruent conditions. The incongruence [negative × smile] elicited the least positive emotion, confidence level, and supply quantity. Our results indicate that incongruent sensory information increases activity in the parietal lobe, which may be a basis for mentalizing.